Cognitive impairment in paediatric multiple sclerosis patients is not related to cortical lesions. (June 2015) - Rocca, Maria A; De Meo, Ermelinda; Amato, Maria P; Copetti, Massimiliano; Moiola, Lucia; Ghezzi, Angelo; Veggiotti, Pierangelo; Capra, Ruggero; Fiorino, Agnese; Pippolo, Lorena; Pera, Maria C; Falini, Andrea; et al.
We investigated the contribution of cortical lesions to cognitive impairment in 41 paediatric MS patients. Thirteen (32%) paediatric MS patients were considered as cognitively impaired. T2-hyperintense and T1-hypointense white matter lesion volumes did not differ between cognitively impaired and cognitively preserved MS patients. Cortical lesions number, cortical lesions volume and grey matter volume did not differ between cognitively impaired and cognitively preserved patients, whereas white matter volume was significantly lower in cognitively impaired versus cognitively preserved MS patients ( p =0.01). Contrary to adult MS, cortical lesions do not seem to contribute to cognitive impairment in paediatric MS patients, which is likely driven by white matter damage.